2009
DOI: 10.1093/ilar.50.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Consequences of Sleep-Disordered Breathing: Contribution of Animal Models to Understanding of the Human Disease

Abstract: Sleep-disordered breathing, and particularly the highly prevalent obstructive sleep apnea syndrome, is a multicomponent disorder combining intermittent hypoxia (IH), sleep fragmentation, and obstructed respiratory efforts. It is frequently associated with comorbidities and leads to numerous complications, including cardiovascular consequences that are conditioned by genetic predisposition and environment. The complexity of the disease and the reduced possibilities for patient investigations, especially at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 233 publications
(298 reference statements)
0
122
0
1
Order By: Relevance
“…Fraction of inspired oxygen in the hypoxic chambers was measured with a gas analyzer (ML206; ADInstruments) throughout the experiment. The IH stimulus consisted of a 60‐second cycle, with 30 seconds of hypoxia (hypoxic plateau at 5% fraction of inspired oxygen) and 30 seconds of normoxia (normoxic plateau at 21% fraction of inspired oxygen), as described 22. Normoxic mice were exposed to air flow turbulences related to gas circulation and noise stimuli similar to those undergone by animals submitted to IH.…”
Section: Methodsmentioning
confidence: 99%
“…Fraction of inspired oxygen in the hypoxic chambers was measured with a gas analyzer (ML206; ADInstruments) throughout the experiment. The IH stimulus consisted of a 60‐second cycle, with 30 seconds of hypoxia (hypoxic plateau at 5% fraction of inspired oxygen) and 30 seconds of normoxia (normoxic plateau at 21% fraction of inspired oxygen), as described 22. Normoxic mice were exposed to air flow turbulences related to gas circulation and noise stimuli similar to those undergone by animals submitted to IH.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is well established that atherosclerosis is a chronic inflammatory disease 13 , and there is growing evidence that OSA is a chronic low grade inflammation. Therefore, IH-induced inflammation could be an additional link between OSA and atherosclerosis 9 , without the use of a dyslipidemic diet and even after a short-term of IH exposure, as we previously showed that 14 days of IH were sufficient to induce vascular alterations 14,15 .…”
Section: Introductionmentioning
confidence: 91%
“…IH was performed in experimental cages accommodating 10 mice each, as previously described 15 . The animals were exposed to IH (cyclic 21-5% FiO 2 , 60s cycle, both normoxic and hypoxic phases for 30s, 8h/day during daytime).…”
Section: Intermittent Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations